Gambaran Tingkat Pengetahuan Tenaga Kefarmasian Tentang Penyerahan Obat Keras Tanpa Resep Dokter di Apotek Desa Waimital - Zidna Di’inina Fakaubun; Azril Mahulauw; Dzulfikri Mewar (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Introduction Hard drugs are drugs that have hard properties and if used carelessly or not according to the rules, can cause dangerous side effects and even poison the body, aggravate the disease, trigger the emergence of other diseases, to cause damage to body organs and death. Hard drugs are drugs that can only be obtained by prescription. Its characteristics are marked with a red round circle with a black border with the letter K in the middle that touches the border. This drug should only be sold in pharmacies and must be prescribed by a doctor at the time of buying it. While Mandatory Pharmacy Drugs (OWA) are some hard drugs that can be submitted without a doctor's prescription, but must be submitted by a Pharmacist at the pharmacy. This research method uses qualitative descriptive research design. What was used was total sampling with the measuring instrument used, namely a questionnaire with the number of samples being 15 respondents who became pharmaceutical personnel at the pharmacy. The results of the study showed that for the variable level of knowledge of pharmaceutical personnel with good categories amounted to 12 respondents with a percentage (80.0%) and enough 3 respondents with a percentage (20.0%), Kesimplant from the results of the level of knowledge of pharmaceutical personnel at pharmacies Waimital Village, Kairatu District, West Seram was good because pharmaceutical personnel knew information about hard drugs without a prescription and it was known that the pharmacist profession and the pharmacist assistant have the same level of understanding.